Impaired Learning and Memory Ability Induced by a Bilaterally Hippocampal Injection of Streptozotocin in Mice: Involved With the Adaptive Changes of Synaptic Plasticity - Qi, Cong-Cong; Chen, Xing-Xing; Gao, Xin-Ran; Xu, Jing-Xian; Liu, Sen; Ge, Jin-Fang (Frontiers in Aging Neuroscience, 2021)
Background: Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive cognitive decline, psychiatric symptoms and behavioral disorders, resulting in disability and loss of self-sufficiency. Objective: To establish an AD-like mice model, investigate the behavioral performance, and explore the potential mechanism. Methods: Streptozotocin (STZ, 3 mg/kg) was microinjected bilaterally into the dorsal hippocampus of C57BL /6 mice, and the behavioral performance was observed. The serum concentrations of insulin and nesfatin-1 were measured by ELISA, and the activation of hippocampal microglia and astrocytes was assessed by immunohistochemistry. The protein expression of several molecular associated with the regulation of synaptic plasticity in the hippocampus and the prefrontal cortex (PFC) was detected via western blotting. Results: The STZ-microinjected model mice showed a slower bodyweight gain and higher serum concentration of insulin and nesfatin-1. Although there was no significant difference between groups with regard to the ability of balance and motor coordination, the model mice presented a decline of spontaneous movement and exploratory behavior, together with an impairment of learning and memory ability. Increased activated microglia was aggregated in the hippocampal dentate gyrus of model mice, together with an increase abundance of Aβ1-42 and Tau in the hippocampus and PFC. Moreover, the protein expression of NMDAR2A, NMDAR2B, SynGAP, PSD95, BDNF, and p-β-catenin/β-catenin were remarkably decreased in the hippocampus and the PFC of model mice, and the expression of p-GSK-3β (ser9)/GSK-3β were reduced in the hippocampus. Conclusion: A bilateral hippocampal microinjection of STZ could induce not only AD-like behavioral performance in mice, but also adaptive changes of synaptic plasticity against neuroinflammatory and endocrinal injuries. The underlying mechanisms might be associated with the imbalanced expression of the key proteins of Wnt signaling pathway in the hippocampus and the PFC.